AXIN2 expression predicts prostate cancer recurrence and regulates invasion and tumor growth. Issue 6 (15th January 2016) - Hu, Brian R.; Fairey, Adrian S.; Madhav, Anisha; Yang, Dongyun; Li, Meng; Groshen, Susan; Stephens, Craig; Kim, Philip H.; Virk, Navneet; Wang, Lina; Martin, Sue Ellen; Erho, Nicholas; et al.
Abstract : BACKGROUND: Treatment of prostate cancer (PCa) may be improved by identifying biological mechanisms of tumor growth that directly impact clinical disease progression. We investigated whether genes associated with a highly tumorigenic, drug resistant, progenitor phenotype impact PCa biology and recurrence. METHODS: Radical prostatectomy (RP) specimens (±disease recurrence, N = 276) were analyzed by qRT‐PCR to quantify expression of genes associated with self‐renewal, drug resistance, and tumorigenicity in prior studies. Associations between gene expression and PCa recurrence were confirmed by bootstrap internal validation and by external validation in independent cohorts (total N = 675) and in silico. siRNA knockdown and lentiviral overexpression were used to determine the effect of gene expression on PCa invasion, proliferation, and tumor growth. RESULTS: Four candidate genes were differentially expressed in PCa recurrence. Of these, low AXIN2 expression was internally validated in the discovery cohort. Validation in external cohorts and in silico demonstrated that low AXIN2 was independently associated with more aggressive PCa, biochemical recurrence, and metastasis‐free survival after RP. Functionally, siRNA‐mediated depletion of AXIN2 significantly increased invasiveness, proliferation, and tumor growth. Conversely, ectopic overexpression of AXIN2 significantly reduced invasiveness, proliferation, and tumor growth. CONCLUSIONS: Low AXIN2 expression was associated with PCa recurrence after RP in our test population as well as in external validation cohorts, and its expression levels in PCa cells significantly impacted invasiveness, proliferation, and tumor growth. Given these novel roles, further study of AXIN2 in PCa may yield promising new predictive and therapeutic strategies. Prostate 76:597–608, 2016 . © 2016 Wiley Periodicals, Inc.